A Comparative Study of Urdu Literary Journals With Reference To Their Special Numbers on Humour and Satire - Waqar Azeem, Fahad; Abbas, Muzaffar (sourcecoder, 2022)
The first literary journal of Urdu was published on 1st September, 1847 A.D. known as "Khair Khah e Hind" later renamed as "Mohib e Hind". During 2nd and 3rd decade of twentieth century A.D., some renowned Urdu journals were issued by some persons having great taste of Urdu literature. These journals include "Humayun", "Nerang e Khayal","Nigar", "Adabi Dunya", "Adab e Latif" etc. These journals set a tradition of issuing special numbers, which also include issuance of special numbers on "Humour and Satire". The role played by these special numbers for promoting humour and satire in Urdu literature has been ignored by the researchers, which is being brought in limelight by this research article.